2020
DOI: 10.1002/pat.4903
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient flame retardant poly(lactic acid) using imidazole phosphate poly(ionic liquid)

Abstract: Because of good thermal stability, nonflammability and rich structural designability, ionic liquids (ILs) have been used as flame retardants for poly(lactic acid) (PLA). However, as a small molecule, IL has the disadvantages of poor thermal stability and water resistance, and so on. In this paper, an imidazole‐type poly(ionic liquid) (PIL) containing a phosphate anion was synthesized using 1‐vinylimidazole, triethyl phosphate, and 1,2‐divinylbenzene and marked as PDVE[DEP]. The PDVE[DEP] was used to improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…The PLLA and PLLA/PDLA sample almost do not have any residues, while the samples after adding ADP exhibit the char barrier cover on the top. Moreover, the EHC values of PLLA/PDLA/ADP sample reduced from 20.21 to 17.18, representing the incomplete combustion and the potential gas phase mechanism from phosphorus-containing FR . The char residues after CCT are shown in Table .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The PLLA and PLLA/PDLA sample almost do not have any residues, while the samples after adding ADP exhibit the char barrier cover on the top. Moreover, the EHC values of PLLA/PDLA/ADP sample reduced from 20.21 to 17.18, representing the incomplete combustion and the potential gas phase mechanism from phosphorus-containing FR . The char residues after CCT are shown in Table .…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, the EHC values of PLLA/PDLA/ADP sample reduced from 20.21 to 17.18, representing the incomplete combustion and the potential gas phase mechanism from phosphorus-containing FR. 22 The char residues after CCT are shown in Table 3 . With the increase of the ADP content, the char residue increases.…”
Section: Resultsmentioning
confidence: 99%
“…As presented in Figure 2d, PBPP exhibited excellent flame retardant efficiency and significantly enhanced the thermal stability of PLA composites compared to reported flame retardants. [27][28][29][30][31][32][33][34][35] The above comparisons indicated that PLA/PBPP composites achieved a relatively optimum balance between flame retardancy and thermal stability, showing expansive application prospects in some key fields. The influence of phosphate ester flame retardant PBPP on the crystallization properties of PLA composites was studied by DSC tests.…”
Section: Thermal and Crystallization Behavior Analysis Of Pla/pbpp Co...mentioning
confidence: 99%
“…Additionally, ILs are promising FRs because of their tunable chemical structure and highly flexible molecular design of both anions and cations 19,20 . It is widely reported that several flame‐retarding elements and groups, such as phosphorous, sulfur, and polyoxometalate cluster, have been introduced into ILs to improve the flame retardancy of EPs.…”
Section: Introductionmentioning
confidence: 99%